Postcolonial Trauma in Athol Fugard’s the Train Driver - Baqer , Zahraa Adnan; Termizi, Arbaayah binti Ali; Amin, Hasyimah binti Mohd (Journal of Ecohumanism, 2024)
This paper examines postcolonial trauma in Athol Fugard’s The Train Driver. The study designates the core conceptual nuances of trauma and how it intensified in the course of the play. It draws on Fugard’s utilization of the dramatic incidents and the characters’ dialogues as mere incarnations of post-colonialism in South Africa where psychic trauma maturely develops and reaches its highest point. Hence, the study follows a textual-contextual interpretation of the play’s setting, characters, and dialogues which reflect the true essence of hegemonic post-colonialism in South Africa. These elements with the subject of the study’s methodology which applies a close reading of postcolonial trauma via pursuing a textual analysis of Fugard’s depiction of the South African native who suffered from severe apartheid. On that account, Dominick LaCapra’s concept of trauma will be polarized in the analysis for the sake of delving deep into the lurking impetus of the characters’ psychic trauma affected by social circumferences. Such circumferences will be analyzed as the regional setting in which the postcolonial encounter between the colonized and the colonizers takes place. In the long run, the play’s dialogues will be explored as the authentic exemplification of postcolonial trauma since the characters reveal their psychic trauma by dint of their dialogues.